(3LGeY GdebGUO aj TQM GdbhGYOs - (3GdcQcj GdYGedj, CHh GdMSf, GdeMbb GdKGfj, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj GdcQcj GdYGedj, J (B940(3g` (B1534(3es ((3eQJVi Hf GdMSjf Hf GdeQJVi GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3bhdg GdebUO GdKGdK aj GdEbQGQ hajg aUhd, GdChd aj CQcGfg, hajg eWGdH, GdChd GdUjZI GdEbQGQs
(3BNQgG (B:s
(3BNQgG(B: (3hGdMGUd Cf EWdGb GdGSJfGHI EfeG jMed Ydi GdGSJfGHI aj MGd GdMjGI hgj GdJhcjd hdG jMed Ydi GdhUjI EdG HOdjd jOd Ydi Cf GdJUQa HYO GdehJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 281s
(3GdPQjYI, L(B5: 51s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis